PENTINGNYA MENERAPKAN NILAI-NILAI MORAL KEAGAMAAN PADA ANAK USIA DINI - Munirah, Munirah; Tapu, Zenab Riana (STAI Darul Qalam Tangerang, 2022)
This article aims to reveal how religious values ​​are in early childhood and how religious and moral values ​​are applied in early childhood. The method used in this article is qualitative; type of library research using documents with content analysis data collection. The results of the discussion in this article are education which is an effort that can be taken by humans to change behavior / morals. Moral behavior is the habitual behavior of humans in a group of religious moral values ​​which is very important to be applied to early childhood. In this case parents play a very important role in children's education because parents are the first teachers that are passed in a family environment. The parents' behavior, speech and appearance will be imitated by the children. So, moral education is very important in the family, because the family plays a very important role and is responsible for providing various kinds of stimulation and appropriate guidance so that the next generation will be created and strong